Crack Propagation Law and Failure Characteristics of Coal-Rock Combined Body with the Different Inclination Angle of Prefabricated Fissure. (5th July 2021) - Zhang, Chunlei; Dong, Yun; Feng, Ruimin; Peng, Ningbo; Zhang, Jihua; Wu, Jingke; Shen, Wei
Abstract : Few studies have been conducted on the crack propagation law and failure characteristics of coal-rock combined body (CRCB) with prefabricated fissure. A sliding crack model was firstly presented to analyze the failure law of rock with a single fracture and the influence of the inclination angle of the fracture on the strength of the rock. The RFPA numerical models of the CRCB with different inclination angles of prefabricated fracture were then established to simulate the dynamic change process of crack propagation and shear stress of the CRCB with prefabricated fracture under uniaxial compression. The influence of the inclination angle of the fracture in the rock on the fracture expansion and failure characteristics of CRCB was further analyzed based on the acoustic emission data. The results showed that (1) when 2 β = arctan 1 / μ, σ cw takes the minimum value, and crack initiation is most likely to occur; (2) the strength of coal-rock assemblage shows different changing trends with the fracture inclination angle; (3) the secondary cracks of CRCB with prefabricated fracture of 0°, 15°, and 30° initiated and expanded near the tip of the main crack, and the secondary cracks of 45°, 60°, and 75° initiated and expanded from the tip of the main crack; (4) there are three failure modes of CRCB with prefabricated crack, the double-shear failure mode Λ, the tensile-shear composite failure mode along the fracture surface, and the tensile failure mode along the fracture surface; and (5) intact CRCB and CRCB with prefabricated crack when α = 75 ° and α = 90 ° have strong brittleness, and other CRCB with different prefabricated fracture inclination angles show a certain degree of postpeak plasticity. The results on the mechanical properties and damage characteristics of CRCB are of great significance for the safety and efficient mining of deep coal resources.